Harry Potter and the Chamber of Secrets - Rowling, J. K. (New York : Scholastic, 2002)
When the Chamber of Secrets is opened again at the Hogswart School of Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
Sequel to: Harry Potter and the sorcerer's stone.
Wilson's Children, June 2000
Elem. School Library Collection, June 2000
School Library Journal starred, July 1999
Notable/Best Books (A.L.A.), January 2000
Booklist starred, May 1999
Keywords: Potter, Harry (Fictitious character) -- Fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; England -- Fiction; Potter, Harry (Fictional character) -- Fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Wizards -- Fiction; Magic -- Fiction; School stories; England -- Fiction